"Well, You Are the One Who Decides": Attempting Shared Decision Making at the End of Aphasia Therapy. Issue 2 (April 2018) - Isaksen, Jytte
Abstract : Clinical borderlands manifest themselves through encounters between people deemed to be in need of health care and health care providers (Mattingly, 2010 ). This article addresses the problem of inherent asymmetry in the clinical discourse between clinical providers, such as speech–language pathologists (SLPs), and persons with aphasia. Speech–language pathologists, communicating as experts, tend to dominate the discourse regarding the course of treatment, particularly with clients with aphasia who may lack the necessary communicative skills to participate in decision making. Such patterns of communication were apparent in a study reported here that involved thematic analysis of the views of 12 SLPs regarding involving people with aphasia in shared decision making and in analysis of 33 video recordings of these 12 SLPs and 28 people with aphasia during clinical interactions. Although the SLPs stated that they wanted to involve their clients in decision making and took steps to do so, the discourse sample analysis revealed that the SLPs controlled the interaction through their initiations, topic selection, and presentation of limited choices. Alternatives for supporting greater decision-making participation among people with aphasia with their clinicians are discussed.